Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Its solve the system of equations. you can do substitution or elimination.
There are two kinds of solving but elimination seems best for this system:
-2x-9y=-25
4x+9y=23 (multiplied it by -1 so you can eliminate the variable "Y")
---------------
2x=-2
x=-1 (divide by 2 on each side)
-2(-1)-9y=-25 (insert what you received for what "X" is)
2-9y=-25 (simplify)
-9y=-27 (subtract 2 on each side)
y=3 (divide each side by -9)
There are two kinds of solving but elimination seems best for this system:
-2x-9y=-25
4x+9y=23 (multiplied it by -1 so you can eliminate the variable "Y")
---------------
2x=-2
x=-1 (divide by 2 on each side)
-2(-1)-9y=-25 (insert what you received for what "X" is)
2-9y=-25 (simplify)
-9y=-27 (subtract 2 on each side)
y=3 (divide each side by -9)
Turn them into y=mx+b form
(-2/9)x+25/9 and (-4/9)x+23/9.
Then equate them to each other
(-2/9)x+25/9=(-4/9)x+23/9
Then solve of x
(-2/9)x+(4/9)x = (23/9) - (25/9)
X = -1
Then plug in X and solve for y
Y = (-2/9)(-1) + (25/9)
Y= (27/9)
Y= 3
So your solution is (-1,3)
(-2/9)x+25/9 and (-4/9)x+23/9.
Then equate them to each other
(-2/9)x+25/9=(-4/9)x+23/9
Then solve of x
(-2/9)x+(4/9)x = (23/9) - (25/9)
X = -1
Then plug in X and solve for y
Y = (-2/9)(-1) + (25/9)
Y= (27/9)
Y= 3
So your solution is (-1,3)
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.